Four new species of the genus Philanthaxia Deyrolle, 1864 (Coleoptera: Buprestidae: Thomassetiini) - Bílý, Svatopluk (Zootaxa, 2016)
Descriptions of four new species of the genus Philanthaxia Deyrolle, 1864: P. depressifrons sp. nov. (Vietnam), P.granum sp. nov., P. hanloni sp. nov. and P. purpureifrons sp. nov (all from The Philippines). All described species are illustrated and compared with the similar or sympatric congeners.